A spirited exchange : the wine and brandy trade between France and the Dutch Republic in its Atlantic framework, 1600-1650 - Rahusen, Henriette (Northern world, 2007)
Assesses the impact of the coastal wine and brandy trade on the early modern French, Dutch, and Atlantic economies.